Effects of fadolmidine, an α2‐adrenoceptor agonist, as an adjuvant to spinal bupivacaine on antinociception and motor function in rats and dogs - Tiina Leino; Timo Viitamaa; Jarmo S. Salonen; Ullamari Pesonen; Antti Haapalinna (Wiley, 2021)
Abstract α2‐Adrenoceptor agonists such as clonidine and dexmedetomidine are used as adjuvants to local anesthetics in regional anesthesia. Fadolmidine is an α2‐adrenoceptor agonist developed especially as a spinal analgesic. The current studies investigate the effects of intrathecally administered fadolmidine with a local anesthetic, bupivacaine, on antinociception and motor block in conscious rats and dogs. The antinociceptive effects of intrathecal fadolmidine and bupivacaine alone or in combination were tested in the rat tail‐flick and the dog's skin twitch models. The durations of motor block in rats and in dogs were also assessed. In addition, the effects on sedation, mean arterial blood pressure, heart rate, respiratory rate and body temperature were evaluated in telemetrized dogs. Concentrations of fadolmidine in plasma and spinal cord were determined after intrathecal and intravenous administration in rats. Co‐administration of intrathecal fadolmidine with bupivacaine increased the magnitude and duration of the antinociceptive effects and prolonged motor block without hypotension. The interaction of the antinociceptive effect was synergistic in its nature in rats. Concentration of fadolmidine in plasma was very low after intrathecal dosing. Taken together, these studies show that fadolmidine as an adjuvant to intrathecal bupivacaine provides enhanced sensory‐motor block and enables a reduction of the doses of both drugs. The results indicate that co‐administration of fadolmidine with intrathecal bupivacaine was able to achieve an enhanced antinociceptive effect without hypotension and could thus represent a suitable combination for spinal anesthesia.